Multiple territories in dispute : water policies, participation and Mapuce indigenous rights in Patagonia, Argentina - Moreyra , Alejandra Esther (Wageningen University, 2023)
Tesis para obtener el grado de Doctor of Philosophy, de Wageningen University, en 2009.